Impact of Firm Value, Financial Decisions and Financial Performance on Environmental, Social and Governance Practices Voluntary Disclosure: Evidence from Egypt - Mohamed, Eglal Abdelal Ali (جامعة قناة السويس - كلية التجارة بالاسماعيلية, 2023)
تعمل البورصة جاهدة على تغيير النظرة الحالية لأعمال المسئولية المجتمعية، من كونها مجرد أعمال خيرية لتصبح أنشطة تسهم في الإدارة الكفء للمخاطر المرتبطة بأعمال وركائز الاستدامة الثلاثة وهي البعد البيئي والبعد المجتمعي وبعد الحوكمة Environmental, Social and Governance (ESG) وفي إطار تحقيق هذا النظرة، يتمثل الهدف الرئيسي لهذا البحث في وضع إطار نظري يتعلق باختبار مدي تأثير كلا من قيمة الشركة والقرارات المالية (الرافعة المالية وسياسة توزيع الأرباح)، والأداء المالي (الربحية والسيولة) على الإفصاح الطوعي عن الحوكمة والمسؤولية الاجتماعية لعينة مكونة من ٣٦ شركة من الشركات المدرجة في البورصة المصرية لفترة 7 سنوات (2015- ۲۰۲۱). وقد تم استخدام تحليل المحتوى وتحليل الانحدار بالإضافة إلى حساب مؤشر للإفصاح الطوعي باستخدام عناصر من ESG لقياس مستوى الإفصاح الطوعي في الشركات المصرية، وتكمن أهمية البحث في الاحتياجات المستمرة من قبل العديد من أصحاب المصلحة لزيادة الإفصاح الطوعي وذلك نظرا لأن الإفصاح الإلزامي للشركات أصبح غير كاف لاتخاذ القرارات المالية والغير مالية. أظهرت النتائج وجود ارتباط معنوي بين كلا من الهيكل المالي للشركة وسياسة توزيع الأرباح على الإفصاح الطوعي عن عناصر ESG وأن هناك أيضا ارتباط معنوي بين الأداء المالي للشركة وبين زيادة الإفصاح الطوعي ESG. ووجدت الباحثة أن هناك علاقة معنوية بين الإفصاح عن عناصر ESG وقيمة الشركة، وكذلك علاقة معنوية بين الإفصاح عن عناصر ESG وعناصر الأداء المالية متمثلا في كلا من ربحية وسيولة الشركة، وهذا ما يؤيد ضرورة تضمين أبعاد المسئولية الاجتماعية والبيئية والحوكمة ضمن مسؤوليات إدارة الشركات المصرية لكي تصبح بيانات إلزامية يجب أن تقرر وتفصح عنها الشركات مما يحسن من قيمة الشركة وزيادة كفاءتها وتحسن أدائها المالي، وبالتالي تنشيط سوق رأس المال وتحقيق التنمية الاقتصادية والاجتماعية على المستوى القومي. لذلك توصى الدراسة بضرورة العمل على زيادة الوعي بأهمية تحسين مستوى الإفصاح والشفافية الطوعي عن أعمال الاستدامة (البيئية، والمجتمعية والحوكمة) وكذلك أهمية إضافة أبعاد المحاسبة عن المسئولية الاجتماعية والبيئية ضمن مسؤوليات الإدارة العليا في الشركات حتى تصبح التقارير المالية أكثر شمولا وجودة للمستفيدين منها، وذلك لتحقيق الرشد في اتخاذ القرارات الاقتصادية وتنشيط سوق رأس المال وبالتالي زيادة قيمة الشركة. The concept of ESG, which stands for Environmental, Social, and Governance, has gained significant traction in the business world in recent years. Investors, stakeholders, and customers alike are increasingly interested in knowing how companies operate beyond their financial performance. ESG involves a company's commitment to sustainability, their impact on the environment, their social responsibility, and their corporate governance practices. Firms, therefore, have a need to disclose information related to their ESG practices as a way to demonstrate their commitment to sustainability and build trust with stakeholders. However, the extent to which firms disclose their ESG practices varies significantly. While some companies provide extensive disclosures, others provide only the minimum required by law. The trend of voluntary disclosure of ESG issues has gained momentum among firms as it has been observed that it helps improve stakeholder trust, reduce risks, and promote long-term sustainability. The main aim of this research is to test the impact of five major independent variables, which are firm value, financial decisions (financial leverage and dividend policy), and financial performance (profitability and liquidity), on the extent of voluntary environmental, social governance voluntary disclosure as a dependent variable, while using market performance (Tobin’s Q) and firm size as control variables for a sample consisting of 36 Egyptian listed firms for the period of 7 years (2015–2021). The research hypotheses are examined using both content analysis and OLS regression analysis. Moreover, an overall voluntary disclosure index was constructed to measure the level of disclosure in the Egyptian firms. The results indicate that the initiatives of voluntary disclosure have been under global scrutiny since the last two decades, owing to various stakeholders’ persistent needs to be more informed about their corporations, as mandatory corporate disclosure nowadays is insufficient. The statistical results show a significant positive correlation between dividend policy, profitability, and liquidity and ESG voluntary disclosure, an indication that financial performance and ESG voluntary disclosure have become increasingly intertwined as investors demand greater transparency and accountability from companies. ESG factors are no longer considered optional add-ons, but rather crucial components of a company's long-term financial success. By voluntarily disclosing their ESG practices, companies can attract socially responsible investors and demonstrate their commitment to sustainable growth. The availability of standardized ESG reporting frameworks also makes it easier for stakeholders to evaluate and compare the performance of different companies. Ultimately, robust ESG disclosure can enhance a company's reputation, mitigate risks, and improve long-term financial performance. In addition, results found that there is a significant positive relationship between ESG voluntary disclosure and firm value. Companies that provide greater disclosure about their ESG practices are perceived as more responsible and are more likely to attract socially responsible investors. This ultimately leads to an increase in firm value. Additionally, ESG disclosure can mitigate the negative impact of environmental and social risks and improve a company's reputation, customer loyalty, and employee satisfaction. The findings show a strong correlation between the extent of ESG disclosure and business value, showing that stakeholder trust, transparency, and accountability all increase firm value.
Keywords: الإفصاح الطوعي -- الأداء المالي -- سوق رأس المال -- القيمة السوقية -- الشركات المصرية